Metaphysical Separatism and Its Discontents: Review of Kelly Oliver, Animal Lessons: How They Teach Us to Be Human - Noll, Samantha (Humanimalia, 2011)
Kelly Oliver. Animal Lessons: How They Teach Us to Be Human. New York: Columbia University Press, 2009. 376 pp. 29.50 pb